PLCζ is the physiological trigger of the Ca(2+) oscillations that induce embryogenesis in mammals but offspring can be conceived in its absence - Hachem, A; Godwin, J; Ruas, M; Lee, H; Buitrago, M; Ardestani, G; Bassett, A; Fox, S; Navarrete, F; de Sutter, P; Heindryckx, B; Fissore, R; et al. (Company of Biologists, 2017)
Activation of the egg by the sperm is the first, vital stage of embryogenesis. The sperm protein PLCζ has been proposed as the physiological agent that triggers the Ca(2+) oscillations that normally initiate embryogenesis. Consistent with this, recombinant PLCζ induces Ca(2+) oscillations in eggs and debilitating mutations in the PLCZ1 gene are associated with infertility in men. However, there has been no evidence that gene knockout of PLCζ abolishes the ability of sperm to induce Ca(2+) oscillations in eggs. Here we show that sperm derived from Plcz1(-/-) males fail to trigger Ca(2+) oscillations in eggs, cause polyspermy, and thus demonstrate that PLCζ is the physiological trigger of these Ca(2+) oscillations. Remarkably, some eggs fertilized by PLCζ-null sperm can develop, albeit at greatly reduced efficiency, and after a significant time-delay. In addition, Plcz1(-/-) males are subfertile but not sterile, suggesting that in PLCζ's absence, eventual, spontaneous egg activation can occur via an alternative route. This is the first demonstration that in vivo fertilization without the normal physiological trigger of egg activation can result in offspring. PLCζ-null sperm now make it possible to resolve long-standing questions in fertilization biology, and test the efficacy and safety of procedures used to treat human infertility.